2017
DOI: 10.32677/ijch.2017.v04.i04.044
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-associated immune thrombocytopenic purpura in a child with bleeding manifestations with review of literature

Abstract: Chickenpox is a benign and self-limiting viral exanthematous infection, but sometimes it may be associated with complications. Mild thrombocytopenia occurs in 1-2% of children with varicella, but severe immune-mediated thrombocytopenia associated with bleeding is a rare complication. Various other mechanisms for thrombocytopenia have been implicated-decreased bone marrow production of platelets, disseminated intravascular coagulation, virally-induced platelet aggregation followed by phagocytosis or lysis, dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One of the hematological complications reported is ITP 8 . Several studies have shown the association between chickenpox and ITP in both children and adults 1,9 . In this case, we presented a rare occurrence of simultaneous chickenpox and ITP.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…One of the hematological complications reported is ITP 8 . Several studies have shown the association between chickenpox and ITP in both children and adults 1,9 . In this case, we presented a rare occurrence of simultaneous chickenpox and ITP.…”
Section: Discussionmentioning
confidence: 66%
“…8 Several studies have shown the association between chickenpox and ITP in both children and adults. 1,9 In this case, we presented a rare occurrence of simultaneous chickenpox and ITP. In review of literature, we found a single case reported with a similar case scenario where a 11-year-old boy presented with hemorrhagic vesicular rashes, petechiae, ecchymosis, epistaxis, hematuria and melena, dated back in 1947.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations